Inequality, human capital, and innovation: China's remaining big problems - Wu, D.; Wu, Z.; Wang, Jinmin; Zhao, Z. (Bioinfo Publications, 2014)
The purpose of this paper is to analyse China’s current problems in inequality and compensation of employees, and their impact on human capital accumulation and innovation, which is one of key factors influencing the sustainable economic growth in China in the following decades. We have analysed the economic reforms in China in the past three decades and discussed the future economic development strategy of China from the perspective of human capital accumulation and innovation